2017
DOI: 10.1038/s41598-017-01935-6
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotophos pesticide affects synthesis and conversion of sex steroids through multiple targets in male goldfish (Carassius auratus)

Abstract: Monocrotophos (MCP) is an organophosphorus pesticide that is median-toxic to fish. MCP pesticide resulted in an increase of 17 beta estradiol following a decrease in testosterone in male goldfish (Carassius auratus). To fully understand the mechanism of MCP pesticide that causes the imbalance between male and female hormones, we determined the levels of plasma cholesterol, spermatic steroidogenic acute regulatory protein mRNA, steroidogenesis enzyme mRNA, plasma sex hormone synthesis intermediates, and effectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…In the present study, StAR expression was decreased in frogs exposed to MC-LR, which may further decrease the level of synthesis of sex hormones, even beyond the mechanisms already discussed. This phenomenon has also been observed for other environmental contaminants such as diethylhexyl phthalate and monocrotophos. , …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, StAR expression was decreased in frogs exposed to MC-LR, which may further decrease the level of synthesis of sex hormones, even beyond the mechanisms already discussed. This phenomenon has also been observed for other environmental contaminants such as diethylhexyl phthalate and monocrotophos. , …”
Section: Resultssupporting
confidence: 58%
“…This phenomenon has also been observed for other environmental contaminants such as diethylhexyl phthalate and monocrotophos. 63,64 In the testes, CH can be converted by CYP11A1 into Pregnenolone (PREG), which can be further converted to PROG by the 3β-HSD enzyme encoded by the HSD3B1 gene. PROG can then be converted by CYP17A1 into 17α-OHP, a vital sex hormone.…”
Section: Mc-lr Disrupts the Hpg Axismentioning
confidence: 99%
“…Pesticide dichlorovas impacts DNA duplication in fish, which causes mutation and hyperpropagation [31] . Tian et al [32] reported that the plasma level of testosterone and 17-beta estradiol in fish decrease with the accumulation of organophosphate pesticides. Neurotoxicity and apoptosis in the brain of the fish Catla catla have been observed by Jindal and Sharma [33] .…”
Section: The Negative Impact Of Pesticides On Aquatic Organismsmentioning
confidence: 99%
“…Bioassays became the widespread mean for the research of 1) the causes and progress of carcinogenesis (Ito et al, 1996;Alden et al, 2011;Osimitz et al, 2013) 2) the properties of botanicals for the diverse applications (Agarwal et al, 2014;Prinsloo et al, 2017) and 3) the metabolites of quarantine weed Ambrosia artemisiifolia (Brückner et al, 2003); as well as for 4) the transcriptomic analyses (Nishi et al, 2015); 5) the elucidation of the influence of known and little-familiar agents on the organ-specific accumulation of toxins, the impairment of ontogenesis, genotoxic, mutagenic, teratogenic, and neurotoxic effects (Jirova et al, 2016;Du Gas et al, 2017;Ghribi et al, 2019), endocrine disruptions (Jirova et al, 2016;Tian et al, 2017;Zhang et al, 2018); 6) the improvement of the comprehension about the properties of substances and products of known nature (Osimitz et al, 2013). Besides plant indicators were applied under the investigation of the participation of the vector insects in the propagation of infection (Manachini et al, 2007), and Gammarus fossarum was involved for the research of the trends of the biodistruction of plant litters (Zubrod et al, 2017).…”
Section: Phenomena Under Studiesmentioning
confidence: 99%
“…In some cases these substances are not beneficial, as they can exhibit unfavorable influence, e. g., under the contamination of nutritive media; and the especial interests of the cobamines' detection comes just from this reason (Crofts et al, 2014). The examples of other identifiable compounds include lactic acid within the root exudates (Wen et al, 2018), dimethyl, diethyl, diallyl and dipropyl phtalates (Sun et al, 2019), brevetoxins (Fleming et al, 2007), tenzauronic acid -mycotoxin of Alternaria alternata (Zhou et al, 2019), various herbicides, particularly glyphosate (Hong et al, 2017), and monocrotophos (Tian et al, 2017;Zhang et al, 2018). Besides, viruses (Manachini et al, 2007) and prions (Giles et al, 2017) belong to the stimuli of more complex level.…”
Section: Sought Stimulimentioning
confidence: 99%